Determinants of Unemployment: Empirical Evidence from Indonesia - Gea Dwi Asmara; Rahmat Saleh (Widya Cipta: Jurnal Sekretari dan Manajemen, 2024)
Indonesia faces the challenge of a rapidly increasing labor force that is not proportional to the number of jobs available, resulting in unemployment. This study examines the effect of economic growth, inflation, and minimum wage on unemployment in 34 provinces in Indonesia from 2018 to 2022. This research uses secondary data from the Central Bureau of Statistics and Bank Indonesia. The data processing method uses panel data regression with the Fixed Effect model. The results of the analysis show that economic growth and inflation have a negative and significant relationship with unemployment in Indonesia. In contrast, the provincial minimum wage has a positive and significant relationship with unemployment in Indonesia.